Design of the ventilation and air-conditioning system in an office building - Rihl, Franc (JET on-line, 2015)
This article presents an office building within the Brestanica Thermal Power Plant for which a design of the ventilation and air-conditioning system has been made. First, a brief description of the existing heating and cooling system from the aspect of the operation and the investment contribution is made. Then a ventilation and air-conditioning system is designed based on the geometric characteristics and thermal needs of the building. Calculation of heat losses, selection of an appropriate ventilation and air-conditioning unit, and design of a ventilation duct system are included in the design. The entire system is evaluated from the aspect of investment value.
Keywords: air-conditioning; Brestanica; Brestanica Thermal Power Plant; cooling; heating; hlajenje; ogrevanje; poslovne zgradbe; prezračevanje; TEB; termoelektrarna; ventilation; ventilation ducts